Transmisja telewizyjna procesji eucharystycznej. Case study - Szczepaniak, Maciej (Poznańskie Studia Teologiczne, 2011)
The article deals with the issue of television broadcast of religious events and in particular of the accompanying commentary. The case study pertains to the broadcast of the Eucharistic procession during the feast of Corpus Christi in TVP Polonia on June 23, 2011. Analysis of the media message showed that the task of the commentator and producer of the programme should consist in bringing out the rich variety of dimensions of the presented religious event. In the case of the Eucharistic procession those dimensions are first of all cultic, christocentric, sanctifying and history of salvation, and secondly the public and semeiological dimensions of the cultic act. Since the programme of the new evangelization asserts that the Church strives to introduce the issue of the proclamation of the Kingdom of God to the modern world also through mass media, it seems that the postulate of such a television broadcast which would show the true identity of the Christian community is valid and timely.